Faktor yang Berhubungan dengan Kejadian Anemia pada Ibu Hamil di Wilayah Kerja Puskesmas Mpunda Kota Bima - Nurhaidah Nurhaidah; Rostinah Rostinah (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2021)
The results of the Indonesian Health Demographic Survey in 2017 show that the maternal mortality rate that occurs in Indonesia is 305 / 100.000 live births. This figure is still high and quite far from the target of the Sustainable Development Goals program. One of the factors contributing to the high maternal mortality in Indonesia is due to bleeding caused by anemia during pregnancy. The purpose of this study was to determine the factors associated with anemia in pregnant women. The population in this study were all pregnant women who performed pregnancy examinations at the Mpunda Public Health Center in Bima City for the period of April-May 2020. The number of sample data was 121 using purposive collection techniques. Data analysis was performed using the chi-square test and logistic regression. The results showed that there was a relationship between knowledge and Antenatal Care (ANC) visits with a p value of 0.028 and 0.022. Meanwhile, age, parity and consumption pattern of Fe tablets did not correlate with the incidence of anemia in pregnant women with p value > 0.05. The logistic regression test results show that the knowledge variable has the greatest influence on the incidence of anemia in pregnant women with an OR value of 2.385. It is hoped that health workers will provide information about the importance of conducting regular antenatal care and intensify the provision of information counseling and education about anemia, so that pregnant women are expected to be able to prevent, detect and manage anemia independently.